Effect of Petroganic Fertilizer and Growmore Fertilizer on the Growth and Production of Hot Chilli (Capsicum frutescens L.), Dewata 43 F1 Variety - Anton Sulistio; Hery Sutejo, Marisi Napitupulu (Universitas 17 Agustus 1945 Samarinda, 2018)
The purpose of this research is to know the effect of petroganic fertilizer and growmore fertilizer and its interaction on growth and yield of cayenne pepper. The research method used Randomized Complete Design (RAL) in factorial 4 x 3, and replication 5 times, consisting of 2 research factors. Factor I is Petroganic fertilizer (P), consists of 4 levels, namely: (p0) without fertilizer Petroganik (control), (p1) Petroganic fertilizer dosage 1 ton / ha equivalent 42 g / plant, (p2) dose of 2 tons Petroganik fertilizer / ha equivalent 84 g / plant and (p3) Petroganic fertilizer dose 3 ton / ha equal to 120 g / plant. Factor II is Growmore fertilizer (D) consisting of 3 levels ie: (d0) without Growmore fertilizer concentration, (d1) Growmore fertilizer concentration 2 g / l.air and (d2) Growmore fertilizer concentration 4 g / l. water.The results showed that the treatment of Petroganik fertilizer significantly affected the age of flowering. Very significant effect on plant height aged 15 days, age 30 days, age 45 days after planting, harvest age, number of fruit per plant and weight of fruit per plant. The weight of the heaviest fruit was found in the p3 treatment of 184.33 g / plant, while the lightest fruit weight was found in the treatment of p0 86.53 g / plant. Growmore fertilizer treatment has no significant effect on plant height age 45 days, flowering age, harvest age and number of fruit per plant. Significant effect on the weight of fruit per plant. Very significant effect on plant height. Interaction treatment of fertilizer Petroganik and fertilizer Growmore very significant effect on plant height, flowering age, harvest age, number of fruit and fruit weight per plant.